Interdisciplinarity and Indigenous Language Media: Understanding Language Choices in Zimbabwe’s Media - Mpofu, Phillip; Salawu, Abiodun (Routledge, 2021)
Indigenous language media research by linguists in Zimbabwe is generally epitomised by animated arguments which disapprove of the dominance of English and marginalisation of indigenous languages in broadcast and print media. Considering the communicative and cultural imperatives for indigenous language media in post-independence African nation-states, including indigenous languages in the media is paramount. However, whilst the need to protect indigenous languages and the effects of global spread of English hegemony have attracted considerable scholarly attention, leading factors that shape language attitudes and language choices in the media are underspecified, and in some cases not specified. Applying the interdisciplinary research approach, this article maintains that an interdisciplinary approach provides the foundation for developing eclectic theory. This enhances the comprehension of historical, socio-political, economic, technological and other factors which determine language choices in broadcast and print media.